Pectinesterase extraction from guava - Ashraf, Fayyaz; Ali, Asbi (Universiti Putra Malaysia Press, 1993)
Pectinesterase (PE) was extracted from guava (Vietnamese variety) fruit and assayed. pH and NaCl concentration influenced the extraction process ofPE from this fruit. The highest PE extraction value at pH 8.0 and with 1. 75M NaCl solution was 2.5 micro-equivalent COOH/min/ml crude extract.